IMPROVING ENGLISH SKILLS THROUGH THE STUDENTS’ INTEREST AND LEARNING STYLE - Paonganan, Anissa Citra (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The objective of this research is to find the way to improve English skill through application students’ learning style and interest. The research method was qualitative descriptive. The participants of the students were the twelfth-class students of Senior High School in a remote area in Tana Toraja. In teaching-learning process, the teacher must know the best way to teach the students. One of the ways that the teacher can use is firstly knowing students learning style and interest. Hence, the teacher can adapt the strategy in teaching. The research use VARK style and DISC test. The result of this research found that the most frequently used of students’ learning style and interest were reading-writing style and conscientiousness. It can be concluded that students’ interest and learning style has a relation, so when the teacher teaches, they should have a strategi in teaching and also it is better when know the students’ preference of learning style and interest. In other hand, the students have the strategy in teaching learning process, kind, friendly. Hence, the students do not hesitate to ask the students